The Newspaper Headline in the Digital Reality: From ˋˋHook’’ to Text Surrogate - Anisimov, Roman Yurievich (KnE Social Sciences, 2021)
Modern print media, for the most part, have a representation in the Internet, and the headings of articles turn into clickable links that the reader can click on to decide whether to read or not to read this text. As a result, a number of media outlets followed the path of ‘flashy’ headlines that do not predict the content of the text, but attract the attention of a potential reader. Such headings go back to the structure of the text adopted in the Byzantine rhetorical tradition: the beginning of the text was the first sign that attracted attention. Other media outlets choose the headline strategy as “ersatz text”: the headline is a concise summary of the text. In the context of digital text consumption, such a strategy is more beneficial for the consumer: by the title, he can already read the contents of the text and not open it if necessary. This strategy inherits the Roman tradition of the beginning of the text: in Quintilian’s scheme it was assumed that the first character of the text is a short retelling-announcement, designed to unite the audience and allowing making a decision whether or not to perceive this text. An analysis of the latest headlines in digital versions of Russian and English newspapers showed that the first strategy that goes back to the rhetoric of Byzantium prevails in Russia, and the second strategy that goes back to the rhetoric of the Roman Empire prevails in Great Britain and the USA. This allows us to talk about the continuation of the traditions of the cultural paradigm in the era of digitalization and the continuity of the cultural code. Keywords: mass media, newspaper language, headline, text, semiotics